An Assessment of digital financial literacy of rural people in the state of Kerala - Nasira Banu M. (Research and Postgraduate Department of Economics E.M.E.A. College of Arts and Science, 2025)
Financial services have changed a lot with the invention and intervention of technology in all ways and means. Notable changes have taken place in banking and financial services due to digitalization. There is an increasing requirement for financial knowledge and literacy, at least a minimal level of necessary digital financial awareness and technological awareness and skills in this twenty-first century, as technological innovations are at a speedier rate and the interconnectivity of the various services is increasing. Therefore, digital financial literacy has assumed a greater significance in the 21st century due to the complex and varied financial services, the prevalence of fraudulent schemes, and the deregulation of regulators and government policies. It is considered an integral part of life skills, and the inability to access or use such services has effectively become an obstacle for individual, community, and economic development. Though most households hold a bank account, they are unaware of the many financial services, facilities and investment provisions due to their lack of financial knowledge, unsatisfactory and adverse financial behaviour, and negative attitudes. This is a challenge due to limited access to financial services available to rural and backwards areas and poor people, together with a lack of digital financial literacy and awareness about digitally provided services. However, the picture is a little different for rural areas. Internet penetration in rural areas is low as compared to urban areas. People from rural areas have a low internet self-efficacy factor. They are not aware of the different features of the Internet and do not know how to operate the Internet for various online activities. There is a strong need to introduce schemes or plans for the digitalization of rural India. Thus, digital financial literacy is a prerequisite for its effective inclusion and poses challenges for policymakers. This research study, entitled “An Assessment of Digital Financial Literacy of Rural People in the State of Kerala”, is relevant in this context. Thus, the study tries to understand digital financial literacy initiatives implemented by various stakeholders in India, especially in the State of Kerala. It examines the demand-side and supply-side aspects of digital financial literacy. It also measures digital financial literacy and identifies its socio-economic and demographic determinants in rural areas of Kerala. Besides these objectives, it analyzes the impact of digital financial literacy on the usage of digital financial services and explores the reasons, challenges and barriers that rural households face regarding digital financial literacy in Kerala. In this study, both primary and secondary data were collected and used to assess the digital financial literacy of rural people in the State of Kerala. The interview schedule was developed to collect primary data from rural people in Kerala. Out of 14 districts of Kerala, three districts, namely Wayanad, Malappuram, and Ernakulam, have been selected for the study based on the rural population. Two Taluks were chosen from each selected district based on the proportion of the rural population. Two Panchayats were selected from every taluk using the same criterion. A proportionate sampling technique randomly selects a sample (respondents) from each chosen Panchayat. For the determination of the sample size, the study used the formula developed by Yamane 1967 and therefore, 400 samples were selected accordingly. The study used two forces of demand and supply that are critical for determining digital financial literacy. The demand side of the digital financial literacy study considered dimensions like digital financial aptitude, digital financial awareness, digital financial attitude & behaviour and digital financial affordability. The supply side considered the dimensions from the 'financial service providers', namely the availability of digital financialinfrastructures and accessibility of digital financial services. A composite index of digital financial literacy is constructed where several dimensions of digital financial literacy are used to assess the extent of its level. For estimating the Digital Financial Literacy Index (DFLI), three core dimensions were used, namely digital financial aptitude, digital financial awareness and digital financial attitude and behaviour. The independent t-test and One-way ANOVA test were used to determine the statistically significant differences between the values of different parameters, i.e. demographic, socio-economic and digital financial literacy. The ordinal logistic regression model has been used to identify the factors contributing to variations in digital financial literacy. The study also investigates the role of digital financial literacy in enhancing the usage of digital financial services (DFS) by employing structural equation modelling (SEM). The study found an overall digital financial literacy index of 0.39, showing a just satisfactory level of digital financial literacy in the state's rural areas. Malappuram has the highest digital financial literacy index (0.45) compared to other districts, followed by Ernakulam (0.39). Wayanad lags with a comparatively lower index (0.34), showing the respondents' lower understanding nd usage of these tools. The results of the ordinal logistic regression model show that the key determinants include age, education level, caste, occupation, income, ration category, and articipation in MGNREGS. Younger individuals, those with higher education, salaried or self-employed people, and higher-income earners are more likely to have better digital financial literacy. The study highlighted the critical role of digital financial literacy in improving the usage of digital financial services among rural households in Kerala by SEM. The findings show that awareness of digital financial services is the most significant determinant among the various dimensions of digital financial literacy, with a strong positive influence on the usage of these financial services. Awareness of digital financial risks also emerged as a critical factor, underlining the importance of equipping users with the knowledge. The dimension of digital financial aptitude showed a oderately positive effect on the usage of digital financial services. Interestingly, though theoretically critical, digital financial attitude and behaviour did not show a statistically significant effect. The most common reasons for digital financial illiteracy include the lack of financial education in schools, a lack of awareness, and a lack of confidence in using digital financial services. Other 1actors like poverty, unemployment, and religious beliefs are less frequently cited as causes. The most significant challenge is the lack of financial knowledge and skills, followed by a idespread lack of awareness and concerns over the risk of financial loss and security issues. Other challenges include a lack of income, trust in digital services, and poor internet connectivity. Based on the findings, the study recommends specific policy measures and interventions for stakeholders. These include implementing comprehensive and targeted digital financial literacy programs, along with awareness campaigns to enhance digital financial knowledge among rural populations in Kerala. Such efforts will promote effective and inclusive financial inclusion in the state
Keywords: Digital Financial Literacy; Digital Financial Aptitude; Digital Financial Awareness; Digital Financial Attitude & Behaviour; Digital Financial Affordability; Availability of Digital Financial Infrastructures; Accessibility of Digital Financial Services; Structural Equation Modelling; Ordinal Logistic Regression Model.